Preferensi Masyarakat Terhadap Agroindustri Kerupuk Sagu Melalui Pendekatan Uji Organoleptik - Asriani; Ahmad Hamundu; Dhian Herdhiansyah (Universitas Djuanda, 2023)
Sago crackers are a local food agroindustry product that is being developed into food made from sago to support food diversification programs. This study aims to describe sago crackers' processing and test consumer preferences for sago crackers to develop the sago agroindustry. Respondents used by student consumers and the general public were 20 consumers using the five senses in the form of taste, aroma, texture, color, and packaging. The consumer's preference level test was conducted through an organoleptic approach test. The analytical technique used is descriptive quantitative using a Likert scale. The test results showed that the assessment of sago cracker products with the highest taste attribute was 45% (like), the highest texture rating was 56% (like), the highest aroma rating was 46% (like), and the highest color rating was 45% (neutral). Meanwhile, the highest packaging attribute assessment was 60% (do not like). Thus, consumer preferences for the attributes of crackers are, on average good, except for the packaging attributes, which are not good, so the packaging attributes need to be improved.